Fever of unknown origin: a clinical mask of malignant peritoneal mesothelioma - Hermann, Jacek; Bajko, Grzegorz; Stajgis, Marek; Szmeja, Jacek; Kościński, Tomasz; Drews, Michał (Contemporary Oncology/Współczesna Onkologia, 2012)
The authors present a patient suffering from malignant peritoneal mesothelioma. Differential diagnosis has become the major concern in the fatally ill patient. Pain, increasing abdominal girth, anorexia and weight loss, and recurrent ascites are the most frequent presenting symptoms. In this patient, fever of unknown origin was a clinical mask of mesothelioma. The diagnostic process was focused on infections and collagen-vascular diseases since they are the most common causes of the systemic inflammatory response syndrome. However, persistent pyrexia can also occur, less frequently, in the course of any malignant disease.